KARAKTERISTIK MINERALISASI BIJIH EMAS PADA PROSPEK HARGOSARI, KECAMATAN TIRTOMOYO, KABUPATEN WONOGIRI, PROVINSI JAWA TENGAH - Arifudin Idrus; Wahyu Hermansyah (KURVATEK, 2021)
Tirtomoyo in Wonogiri district is known as an ore mineralization region, in which one of the prospects occurred is Hargosari. No previous studies on the ore characteristucs have been done. A set of study on Hargosari prospect is aimed to characterize gold mineralization covering some aspects such as mineralogy, textures, ore chemistry and ore forming condition. To achieve the objectives, some research methods were performed suh as mapping, sampling and laboratory analyses for selected samples on term of petrography, ore microscopy and ore chemistry. Oligo-Miocene andesitic lava from Panggang Formation is identified as host rock. Opening system of veins is of jogs type to form en-´echelon tension gash veins. Quartz veins are enveloped by argillic and propylitic alteration zones, in association with pyrite, chalcopyrite, sphalerite, galena, gold, silver, chrysocolla, covellite and hematite. The approximately 5 cm thick quartz veins exhibit massive, swarm, low angle veins and stockwork structures, which is characterized by normal banded, crustiform, comb and saccaroidal textures. The quartz veins contain high base metals of up to 5.45% Cu, 9.9% Pb and 12.85% Zn, with significant grade of gold and silver of up to 3.85 g/t Au dan 395 g/t Ag. From mineral assemblages, the veins might be formed at temperatures of about 250-300°C. On the basis of those mentioned characteristics, gold mineralization in Hargosari prospect is categorized into an intermediate sulfidation epithermal. Keywords: characteristics, gold, epithermal, Hargosari, Wonogiri.